Low prevalence of fluoroquinolone resistance among patients with tuberculosis in the Philippines: results of a national survey. Issue 3 (22nd March 2018) - Lim, Dodge R.; Dean, Anna S.; Taguinod-Santiago, Mary Rosary; Borbe-Reyes, Angeli; Cabibbe, Andrea Maurizio; Zignol, Matteo; Basilio, Ramon P.; Garfin, Anna Marie Celina; Ama, Maria Cecilia G.
Antimicrobial resistance (AMR) represents a global threat to public health and security. Misuse of antibiotics is the leading cause of AMR worldwide. Infections that are typically easily treatable can become life-threatening or even deadly. Multidrug-resistant (MDR) tuberculosis (TB) (defined as resistance to at least rifampicin and isoniazid, the two most powerful first-line anti-TB drugs) and extensively drug-resistant (XDR)-TB (defined as MDR-TB with additional resistance to any fluoroquinolone and a second-line injectable (SLI) agent) are forms of TB that are complex to treat, require longer and more toxic regimens [1], and have considerably worse prognosis and outcome [2, 3]. Resistance to anti-TB drugs poses a major challenge to ending the global TB epidemic by 2030 [4]. To estimate the burden of drug-resistant TB, and plan diagnostic and treatment services, surveillance of drug resistance among TB patients has been conducted worldwide since the 1990s [5]. Prevalence of fluoroquinolone resistance among Filipino TB patients is lower than in other countries in the region http://ow.ly/7ywW30ix74W